1984
DOI: 10.1177/009318538401200406
|View full text |Cite
|
Sign up to set email alerts
|

Factors Correlated with Psychiatric Recommendations of Incompetency and Insanity

Abstract: One hundred and twenty criminal defendants referred to a state hospital forensic unit underwent extensive examinations for the purpose of arriving at psychiatric recommendations regarding competency to stand trial and criminal responsibility. Seventy variables were abstracted from these evaluations via use of a simple checklist. A series of discriminant function analyses utilizing these variables indicated that highly accurate predictions could be made regarding psychiatric recommendations with respect to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 0 publications
7
35
0
Order By: Relevance
“…Many of the circumstances mentioned by the informants in this study as contributing to their violent relapse have been confirmed in other studies within the risk prediction field. These are, for example, separations (Daniel 1984;Hall 1978;Zamble & Quinsey 1997), drug use (Steadman et al 1998;Swanson 1994;Swanson et al 1990), unstable living conditions (Bartels et al 1991;Fisher 1988), and socialization with antisocial companions (Feldmann et al 1990). However, the informants' descriptions illustrate the high degree of variation in how such risk markers may influence a course of events.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the circumstances mentioned by the informants in this study as contributing to their violent relapse have been confirmed in other studies within the risk prediction field. These are, for example, separations (Daniel 1984;Hall 1978;Zamble & Quinsey 1997), drug use (Steadman et al 1998;Swanson 1994;Swanson et al 1990), unstable living conditions (Bartels et al 1991;Fisher 1988), and socialization with antisocial companions (Feldmann et al 1990). However, the informants' descriptions illustrate the high degree of variation in how such risk markers may influence a course of events.…”
Section: Discussionmentioning
confidence: 99%
“…Pasewark, Bogenberger, Gudeman, and Bieber () found significant effects for employment history, with unemployed defendants more likely to be found insane. Cirincione et al () found unmarried defendants were more often adjudicated insane, while Daniel et al () found no significant relationship between evaluator opinions and marital status.…”
Section: Existing Research On Correlates Of Cr Outcomesmentioning
confidence: 99%
“…The relationship between race/ethnicity and CR outcomes is less consistent, with studies divided on whether Whites or non‐Whites are more likely to be found insane (Boehnert, ; Cirincione et al, ; Daniel et al, ; Johnson et al, ; Warren et al, ). These variable findings may be due to jurisdictional factors.…”
Section: Existing Research On Correlates Of Cr Outcomesmentioning
confidence: 99%
See 2 more Smart Citations